Iodine Concentration in Brazilian Drinking Water and Its Possible Contribution to Iodine Intake for Different Physiological Groups - Carina Aparecida Pinto; Edimar Aparecida Filomeno Fontes; Sandra Patricia Crispim; Sarah Aparecida Vieira Ribeiro; Sylvia do Carmo Castro Franceschini; Nathalia Pizato; Franciane Rocha de Faria; Renata Junqueira Pereira; Carolina Abreu de Carvalho; Míriam Carmo Rodrigues Barbosa; Naiara Sperandio; Mariana de Souza Macedo; et al. (Journal of Nutrition and Metabolism)
Objective. The objective is to analyze the concentration of iodine in Brazilian drinking water and its possible contribution to iodine intake for different groups. Methods. Water samples collected from primary healthcare units in eight locations distributed across all five macroregions of Brazil were analyzed. The quantification of iodine in the water samples was done by spectrophotometry (leuco crystal violet method). To classify the degree of iodine concentration, the recommendation of the Ministry of Health (China) was followed since Brazil lacks a classification standard. To verify the possible contribution of drinking water to iodine intake for different groups, the recommended water intake for each group according to the United States Institute of Medicine (2004) was considered. The percentage of iodine in drinking water and its contribution to iodine intake for different physiological groups were calculated based on the estimated average requirement (EAR) of iodine. A descriptive statistical analysis was performed using SPSS version 21.0 and Statistical Analysis Systems (SAS) version 9.2. Results. Significant differences were found between the maximum and minimum concentrations of iodine in water samples from the same location. In Pinhais (south region), the difference was 44.32 μg⋅ L−1; in Viçosa (southeast region), it was 27.86 μg·L−1; in Rondonópolis (midwest region), it was 12.66 μg·L−1; in São Luís (northeast region), it was 11.82 μg·L−1; in Brasilian Federal District (midwest region), it was 10.98 μg·L−1; in Macaé (southeast region), it was 10.14 μg⋅ L−1; in Palmas (north region), it was 4.22 μg·L−1; and in Vitória (southeast region), it was 1.69 μg·L−1. The maximum concentrations of iodine found in the drinking water of Pinhais and Viçosa can contribute more than 70.0% and 50.0%, respectively, to daily iodine intake for all groups. Conclusion. Monitoring the concentration of iodine in drinking water from different locations in each city or Federal District is a preventive measure against inadequate iodine intake and possible adverse changes in population health.